2019
DOI: 10.3390/min9030160
|View full text |Cite
|
Sign up to set email alerts
|

Platiniferous Tetra-Auricupride: A Case Study from the Bolshoy Khailyk Placer Deposit, Western Sayans, Russia

Abstract: Tetra-auricupride, ideally AuCu, represents the only species showing the coexistence of Au with an elevated level of Pt, as in the case of a detrital grain studied structurally for the first time, from an ophiolite-associated placer at Bolshoy Khailyk, western Sayans, Russia. We infer that tetra-auricupride can incorporate as much as ~30 mol. % of a “PtCu” component, apparently without significant modification of the unit cell. The unit-cell parameters of platiniferous tetra-auricupride are: a 2.790(1) Å, c 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The occurrence of a rare Pt-enriched tetra-auricupride was documented by Barkov et al [11] from an ophiolite-associated placer at Bolshoy Khailyk, western Sayans, Russia. The authors, based on the chemical composition and a synchrotron micro-Laue diffraction study, concluded that tetra-auricupride can incorporate as much as~30 mol % of a "PtCu" component, apparently without relevant modification of the unit cell.…”
mentioning
confidence: 80%
“…The occurrence of a rare Pt-enriched tetra-auricupride was documented by Barkov et al [11] from an ophiolite-associated placer at Bolshoy Khailyk, western Sayans, Russia. The authors, based on the chemical composition and a synchrotron micro-Laue diffraction study, concluded that tetra-auricupride can incorporate as much as~30 mol % of a "PtCu" component, apparently without relevant modification of the unit cell.…”
mentioning
confidence: 80%
“…19)Σ0.98S1.02, a bornite-like phase, (Cu4.06Fe1.47)Σ5.53S4.5, and a godlevskite-like phase, Ni9.5S7.5. Less common and rare minerals include sperrylite, a zoned oxide Ru6Fe 3+ 2O15, and an uncommon variety of seleniferous and rhodiferous sperrylite (Pt,Rh)(As,Se,S)2 [1,10].…”
Section: Occurrence and Associated Mineralsmentioning
confidence: 99%
“…The density could not be measured owing to the small The sulfide species observed in the placer are members of the laurite-erlichmanite series, cooperite, bowieite (Cu-rich), a monosulfide-type phase, (Fe 0.40 Ni 0.39 Cu 0.19 ) Σ0.98 S 1.02 , a bornite-like phase, (Cu 4.06 Fe 1.47 ) Σ5.53 S 4.5 , and a godlevskite-like phase, Ni 9.5 S 7.5 . Less common and rare minerals include sperrylite, a zoned oxide Ru 6 Fe 3+ 2 O 15 , and an uncommon variety of seleniferous and rhodiferous sperrylite (Pt,Rh)(As,Se,S) 2 [1,10].…”
Section: Pcsm: Appearance Physical and Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold enriched with platinum has also been identified in drainage and overburden derived samples from Lower Devonian sediments and in minor volcanic rocks of Devon, SW England, considered to have grown from oxidising saline fluids at approximately 100 • C [64]. Gold-platinum-copper alloys have also been described in Russia [65,66] in the placer of the Konder alkaline-ultrabasic massif [65] and in the alluvium along the River Bolshoy Khailyk, western Sayans [66]. Although rare, platinum enrichments are recorded in coal where a source is available [9].…”
Section: Gold (And Platinum) Sourcementioning
confidence: 99%